1993
DOI: 10.1021/j100139a010
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved electronic excitation spectra of the ethoxy ~B .rarw. ~X transition

Abstract: High-resolution electronic excitation spectra of the 0 : and the 9; bands of the near-UV electronic transition of the ethoxy radical have been recorded. The ethoxy radical was produced in a free-jet expansion by photodissociation of ethyl nitrite (CzHsONO). Both spectra have a linewidth of about 400 MHz. A complete rotational analysis of the spectrum indicates that the electronic transition of ethoxy is C-type (perpendicular) and the ground-state spin-rotation splittings are fully resolved, while the excited s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…The jet-cooled LIF excitation spectrum of ethoxy has been reported by several groups [8][9][10] and selected vibrational bands in this spectrum were chosen to obtain the natural lifetimes. The lifetimes were measured using the following procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The jet-cooled LIF excitation spectrum of ethoxy has been reported by several groups [8][9][10] and selected vibrational bands in this spectrum were chosen to obtain the natural lifetimes. The lifetimes were measured using the following procedure.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 In the CO stretch band (see Fig. 9) the rotational transitions appear broader still and some are even split.…”
Section: E Line Broadening and Splittingmentioning
confidence: 97%
“…Theà −X separation of the vibrationless levels (T 00 ) of ethoxy was found to be 364 cm −1 in DF spectroscopy 7,16 and 355(10) cm −1 in a photoelectron study. 17 Simulation of the origin band of theB −X LIF transition with rotational and fine-structure resolution was found to require a perpendicular transition type, 18 which implies that the ground electronic state is of A symmetry. Later studies of the DF 7 and high-resolution LIF spectra 19 of 1-propoxy (1-C 3 H 7 O) and other larger primary alkoxies have shown that all of the conformers with C s symmetry (T-conformers) have ground electron states with A symmetry andà −X separations of 350 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The matrix elements of the rotational Hamiltonian, H Rot , are well-known. 29,30 The spin-rotation Hamiltonian has been examined by many authors 29,[31][32][33][34][35] and can be written as…”
Section: Theorymentioning
confidence: 99%